Critical review of total quality management - Mohd. Yusof, Sha'ri (Faculty of Mechanical Engineering, 1999)
This paper presents a critical review of total quality management (TQM) and the various concepts surrounding it. It starts by reviewing and discussing issues surrounding quality, including its definition, the historical origins of TQM, and the developments that have resulted in the importance that has been placed by many researchers, academics, consultants, industrialists and professionals on TQM. Finally, an integrated TQM model is presented which captures most of the concepts, principles and elements discussed.